2018
DOI: 10.1016/j.neuropsychologia.2018.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Role of context in affective theory of mind in Alzheimer's disease

Abstract: Affective theory of mind (ToM) is defined as the ability to deal with affective mental states. Attributing an affective mental state from a facial expression relies mainly on processes that allow information in the environment to be perceived and decoded. Reasoning processes are required when information is not directly available in the environment (e.g., when making an affective mental state attribution in a social situation where there is no visible facial expression of emotion). Although facial emotion deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 73 publications
(106 reference statements)
1
28
2
Order By: Relevance
“…This disconnect between the cognitive and affective subcomponents of empathy aligns with conclusions from a recent qualitative review (Fischer et al, 2019). Similarly, some studies have found that individuals with AD are impaired in cognitive empathy (Castelli et al, 2011;Dodich et al, 2016;Duclos et al, 2018), while others have found no differences in affective empathy (Dermody et al, 2016;Nash et al, 2007). Importantly, unlike these prior studies, this study used meta-analytic methods which allowed the aggregation of mean effect sizes while controlling for sampling error (the most serious source of artefactual variance), thus providing a clearer understanding of how the different components of ToM and empathy are affected by AD.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This disconnect between the cognitive and affective subcomponents of empathy aligns with conclusions from a recent qualitative review (Fischer et al, 2019). Similarly, some studies have found that individuals with AD are impaired in cognitive empathy (Castelli et al, 2011;Dodich et al, 2016;Duclos et al, 2018), while others have found no differences in affective empathy (Dermody et al, 2016;Nash et al, 2007). Importantly, unlike these prior studies, this study used meta-analytic methods which allowed the aggregation of mean effect sizes while controlling for sampling error (the most serious source of artefactual variance), thus providing a clearer understanding of how the different components of ToM and empathy are affected by AD.…”
Section: Discussionsupporting
confidence: 75%
“…The following studies were excluded because the data were not available (Martinez et al, 2018;Poveda et al, 2017;Rowse et al, 2013;Zaitchik et al, 2006). In certain instances, data were unavailable upon request due to specific participant groups not being assessed on the measures of interest (Cuerva et al, 2001;Dodich et al, 2016;Duclos et al, 2018;Fernandez-Duque, Baird, & Black, 2009;Youmans & Bourgeois, 2010). If participants scored at ceiling or floor on any measure, data for both control and AD participants from the measure in question were not permitted to contribute to the analyses.…”
Section: Data Extractionmentioning
confidence: 99%
“…In this regard, the study by Synn et al16 is notable in demonstrating comparable difficulties on the ToM and “random movement” conditions of the Frith–Happé animations task, suggesting that ambiguity of stimuli and increasingly abstract task demands contribute to ToM impairments in AD 16. By contrast, with the provision of situational and social contexts, ToM deficits in AD are mitigated,79 presumably due to attenuation of the executive and mnemonic task demands. In summary, the bulk of evidence points to a domain-general impairment in ToM, attributable to a primary decline in memory, executive, and general cognitive abilities.…”
Section: Alzheimer’s Disease (Ad)mentioning
confidence: 92%
“…These processes may support the integration and maintenance of relevant information on ToM tasks, as well as facilitating the inference of mental states in the presence or absence of situational cues 77,78. With disease progression, increasing executive, visuospatial, and general cognitive dysfunction likely impact ToM performance, especially on tasks that tax visuospatial abilities or lack explicit situational cues 16,79. In this regard, the study by Synn et al16 is notable in demonstrating comparable difficulties on the ToM and “random movement” conditions of the Frith–Happé animations task, suggesting that ambiguity of stimuli and increasingly abstract task demands contribute to ToM impairments in AD 16.…”
Section: Alzheimer’s Disease (Ad)mentioning
confidence: 99%
See 1 more Smart Citation